1990
DOI: 10.1089/dna.1990.9.499
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of cDNAs Encoding Bovine and Human Lactoperoxidase

Abstract: Peptide sequences obtained from cyanogen bromide fragments of bovine lactoperoxidase (bLPO) were used to design oligonucleotide probes for library screening. These probes were used to screen a cDNA library constructed from bovine mammary tissue. Three overlapping clones were obtained, the longest of which (T3) contained a reading frame of 712 amino acid residues. The encoded amino acid sequence was homologous to those recently reported for myelo-, thyro-, and eosinophil peroxidases. Two possible amino termini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 39 publications
3
53
0
Order By: Relevance
“…As shown in Fig. 4A, Ala489, Phe490, Arg491, Gly493, and His494 are well conserved among all known TPO polypeptides, including pig (Magnusson et al 1987b), mouse (Kotani et al 1993), and rat (Derwahl et al 1989), and also in human (Morishita et al 1987) and mouse myeloperoxidases (Venturelli et al 1989), human eosinophil peroxidase (Ten et al 1989), and human and bovine lactoperoxidases (Dull et al 1990). Phe492, although not conserved among all peroxidases, is conservatively substituted with tyrosine residue in human and mouse myeloperoxidase.…”
Section: Deleterious Effect Of Identified Missense Mutationsmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Fig. 4A, Ala489, Phe490, Arg491, Gly493, and His494 are well conserved among all known TPO polypeptides, including pig (Magnusson et al 1987b), mouse (Kotani et al 1993), and rat (Derwahl et al 1989), and also in human (Morishita et al 1987) and mouse myeloperoxidases (Venturelli et al 1989), human eosinophil peroxidase (Ten et al 1989), and human and bovine lactoperoxidases (Dull et al 1990). Phe492, although not conserved among all peroxidases, is conservatively substituted with tyrosine residue in human and mouse myeloperoxidase.…”
Section: Deleterious Effect Of Identified Missense Mutationsmentioning
confidence: 90%
“…Conserved amino acids are boxed. The numbering of amino acid sequences is adopted from the following references: human TPO, Kimura et al (1987); pig TPO, Magnusson et al (1987b); mouse TPO, Kotani et al (1993); rat TPO, Derwahl et al (1989); human MPO, Morishita et al (1987); mouse MPO, Venturelli et al (1989); human eosinophil peroxidase (EPO), Ten et al (1989); human and bovine lactoperoxidase (LPO), Dull et al (1990).…”
Section: Figurementioning
confidence: 99%
“…Breastfed sucklings, for example, almost exclusively exhibit Bifidobacterium bifidum in their intestine [2]. Milk proteins which are supposed to be responsible for this modulation are for example lysozyme [3,4], lactoperoxidase [5][6][7], lactoferrin [7][8][9] and antibodies [10]. However, in vivo the ingestion of lactoferrin has only a marginal influence on the intestinal microflora [1 1].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the glycosylation level of recombinant protein might also be different between RK13 cells and insect cells. Most of the bLPO extracted from milk showed Asp-101 as the N-terminal amino acid residue (Dull et al 1990;Watanabe et al 2000). However, Watanabe et al (2000) found also that different preparations of bLPO showed a different N-terminal amino acid residue.…”
Section: Discussionmentioning
confidence: 99%